Impact of Multilingualism on Shina Language in Urban Setting: Issues of Language Shift among Youth - Akhtar, Yasmin; Bibi, Maria; Tarnum, Nishat (Journal of Communication and Cultural Trends, 2025)
The present study explores the impact of multilingualism on the Shina language in urban settings and examines issues related to language shift among native speakers of Shina. The sample consists of one hundred urban educated Shina speakers, aged 18 25 years, of both genders, who are studying at universities in Rawalpindi/Islamabad. The study adopts a mixed-method approach, utilizing both quantitative and qualitative methods. Data were collected through a questionnaire and group discussions. The domains used to design the questionnaire and group discussions are based on Sabiha Mansoor’s (1993) ’Punjabi, Urdu, and English in Pakistan: A Sociolinguistic Study’. Shina, an important language spoken in Gilgit-Baltistan, is endangered due to its speakers’ social and economic need to learn English and Urdu for education and employment. The findings reveal that Shina is rarely spoken in the domains of interactions with strangers, social gatherings, and communication with teachers, with the exception of the home domain, where it is spoken by 81% of the respondents. The respondents exhibit negative attitudes toward Shina and positive attitudes toward English and Urdu. In urban settings, where a diverse range of languages coexist, languages inevitably influence each other—a phenomenon also observed in the case of Shina.